Chính sách thúc đẩy tăng trưởng từ kết quả ứng dụng khoa học công nghệ - đổi mới sáng tạo và chuyển đổi số của doanh nghiệp Việt Nam - Nguyễn Khắc Quốc , Bảo; Tô Công Nguyên, Bảo (JOURNAL OF ASIAN BUSINESS AND ECONOMIC STUDIES, 2025)
The article “Digital Transformation - An Important Driving Force for Developing Productive Forces, Perfecting Production Relations, and Bringing the Country into a New Era” by General Secretary and President To Lam, published on the occasion of the 79th anniversary of the National Day of the Socialist Republic of Vietnam (September 2, 1945 - September 2, 2024), clearly emphasizes the critical role of science and technology applications, innovation, and the digital transformation revolution in shaping the nation’s destiny. The post-COVID-19 world is immersed in a whirlwind of instability, marked by multi-dimensional fluctuations in geopolitics, economics, and society. These intertwined challenges create a daunting landscape for many nations, and Vietnam is no exception. Instability has been and continues to creep into every corner of its economy. Amid such an uncertain environment, where opportunity often coexists with danger, the application of science and technology, innovation, and digital transformation emerges as a beacon of hope. This strategy presents opportunities to promote innovation and enhance the competitiveness of the economy's key pillars—enterprises. At its core, the strategy must prioritize science and technology, innovation, and digital transformation as guiding principles, leveraging available resources and the nation’s inherent potential and strategic position.
Keywords: Growth; Science and technology; Innovation; Digital transformation; Enterprises; Vietnam